Annual General Meeting, convened virtually from locations across Turtle Island (Labour / Le Travail, 2023)

The Story of Work, A New History of Humanity - Adams, Roy (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "The Story of Work, A New History of Humanity," by Jan Lucasssen.

Bâtir une GRH inclusive en PME au travers des relations de don/contre-don entre dirigeant et salariés - Adla, Ludivine; Gallego-Roquelaure, Virginie (Relations industrielles / Industrial Relations, 2023)
Cet article vise à comprendre l’émergence et le développement d’une gestion des ressources humaines (GRH) inclusive en PME. Le concept d’inclusion renvoie à l’épanouissement professionnel et à la reconnaissance des salariés (Bonneveux et al., 2020). Cette forme de GRH comporte une visée intégrative dans la mesure où elle offre la possibilité d’améliorer la collaboration notamment entre le dirigeant et ses salariés. Dans cette optique, nous avons mobilisé de façon originale la logique du don de Mauss, couplée à la littérature sur la GRH en PME afin de proposer une nouvelle grille de lecture. À partir du cas emblématique d’une PME, une étude qualitative longitudinale a été menée sur une période de 8 ans. Les résultats soulignent le décalage entre les contre-dons attendus et ceux réellement réalisés par le dirigeant, qui conditionnent in fine l’adonnement des salariés. Ce déséquilibre dans la relation amène à la construction d’une GRH inclusive.
Keywords: GRH; HRM; PME; SMEs; contre-don; counter-gift; don; gift; inclusion; relations; relationships

Left Americana and the Ludlow Monument - Antaya, Sean (Labour / Le Travail, 2023)
Describes the author's visit to the Ludlow Monument in Ludlow, Colorado, that memorializes the 1914 massacre of striking coal miners by national guard and private security forces of the Rockefeller-owned Colorado Iron and Fuel Company. Illustrations are included.

Resilience and Post-Traumatic Growth after Discriminatory Job Loss: The Case of Academics Dismissed after Turkey’s 2016 Coup - Atay, Erhan; Bayraktaroglu, Serkan (Relations industrielles / Industrial Relations, 2023)
This study is about the impact of discriminatory job loss (DJL) on individual attitudes. It is based on interviews with 36 academics who were inequitably and involuntarily fired, and aggressively and punitively discriminated against. We extend previous research on workplace discrimination by exploring the effects of discriminatory job loss on a skilled workforce and by going beyond the job loss itself to examine coping mechanisms, resilience and post-traumatic growth. We found that gratitude, patience and optimism or pessimism about one’s future and career were leading individual factors in the ability to cope with discriminatory job loss. Such coping mechanisms, and their roles in resilience and post-traumatic growth, were described to us by academics in Turkey and abroad.
Keywords: Discriminatory job loss; Perte d'emploi discriminatoire; academic; académique; attitude; career; carrière; discrimination; involuntary job loss; perte d'emploi involontaire

Lessons in Legitimacy: Colonialism, Capitalism, and the Rise of State Schooling in British Columbia - Augustus, Camie (Labour / Le Travail, 2023)
The article reviews the book, "Lessons in Legitimacy: Colonialism, Capitalism, and the Rise of State Schooling in British Columbia," by Sean Carleton.

Pour sortir les allumettières de l’ombre. Les ouvrières de la manufacture d’allumettes E.B. Eddy de Hull (1854-1928) - Baillargeon, Denyse (Labour / Le Travail, 2023)
The article reviews the book, "Pour sortir les allumettières de l’ombre. Les ouvrières de la manufacture d’allumettes E.B. Eddy de Hull (1854-1928)," by Kathleeen Durocher.

Overqualification and Turnover Intention: The Significance of Work-Life Balance for Canadian-Born and Immigrant Employees - Ballesteros-Leiva, Felix; St-Onge, Sylvie; Arcand, Sébastien (Relations industrielles / Industrial Relations, 2023)
Using conservation of resources (COR) theory (Hobfoll, 1989, 2002), we first investigated the direct influence of overqualification on turnover intention. Second, we tested whether the perceived work-life balance affects the relationship between overqualification and turnover intention. To that end, we used questionnaires to conduct independent field studies of two groups of Canadian workers: 227 local human resources professionals and 237 immigrant employees. Both studies confirmed that perceived overqualification increased their intention to quit their jobs. Perceived work-life balance moderated the relationship between overqualification and turnover intention only among the immigrant employees. This paper sheds light on how perceived overqualification can affect the intention to quit a job among local and immigrant employees. It also shows how perceived work-life balance can affect the relationship between perceived overqualification and the intention to quit a job.
Keywords: Canadian-born and immigrant employees; overqualification; turnover intention; work-life balance

Making Mexican Chicago: From Postwar Settlement to the Age of Gentrification - Barajas, Frank P. (Labour / Le Travail, 2023)
The article reviews the book, "Making Mexican Chicago: From Postwar Settlement to the Age of Gentrification," by Mike Amezcua.

A Memory of Irving Abella - Bercuson, David (Labour / Le Travail, 2023)
Pays homage to the life and work of the labour and Jewish studies historian, Irving Abella (1940-2022).

Behind the Scenes: Gender Equality in Local Union Leadership - Bernard Pelletier, Marie-Pier; Le Capitaine, Catherine (Relations industrielles / Industrial Relations, 2023)
This article examines the experiences of local union presidents with respect to gender equality. Based on a qualitative case study of members of union committees dedicated to the status of women and local union presidents working in the Québec education sector, our research points to an unprecedented breakthrough of women serving as local presidents. Nevertheless, the existence of a “triple burden,” the persistence of gender stereotypes and a male union culture, the lack of training and mentoring, and the reliance on solicitation are all hindering the achievement of gender equality. Our research findings also highlight a weak representation of the diversity of social identities within the union organization studied.
Keywords: Union representation; education sector; gender; local presidents; women

Behind-the-scenes: vers l’égalité de genre au sein des présidences syndicales locales? - Bernard Pelletier, Marie-Pier; Le Capitaine, Catherine (Relations industrielles / Industrial Relations, 2023)
Cet article porte sur l’expérience des présidences impliquées dans les organisations syndicales locales au regard de l'égalité de genre. À partir d’une étude de cas qualitative menée auprès des membres de comités syndicaux de la condition féminine et de présidences syndicales locales du secteur de l’éducation du Québec, notre recherche fait valoir une percée sans précédent des femmes siégeant comme présidentes locales. Néanmoins, l’existence d’une « triple tâche », la persistance de stéréotypes de genre et d’une culture syndicale masculine, le manque de formation et de mentorat ainsi que le recours à la sollicitation nuisent à l’atteinte de l’égalité de genre. Nos résultats de recherche font aussi ressortir une faible représentation de la diversité des identités sociales au sein de l’organisation syndicale étudiée.
Keywords: femmes; genre; présidence locale; représentation syndicale; secteur de l’éducation

La grève de toutes les grèves - Bernatchez, Jean-Claude (Revue internationale sur le travail et la société, 2023)
Lancée en mi-novembre 2023, cette grève engage près d’un demi-million de fonctionnaires soit l’essentiel des effectifs des secteurs publics c’est-à-dire, la santé et l’éducation, du primaire au collégial . Elle représente un affrontement historique avec l'État québécois sous deux thématiques essentielles : les salaires et les charges de travail.

Deindustrializing Montreal. Entangled Histories of Race, Residence, and Class - Bérubé, Harold (Labour / Le Travail, 2023)
The article reviews the book, "Deindustrializing Montreal. Entangled Histories of Race, Residence, and Class," by Steven High.

Penal Servitude: Convicts and Long-Term Imprisonment, 1853-1948 - Black, Lynsey (Labour / Le Travail, 2023)
The article reviews the book, "Penal Servitude: Convicts and Long-Term Imprisonment, 1853-1948," by Helen Johnston, Barry Godfrey, and David J. Cox.

Facteurs en Europe. Le syndicalisme face à la libéralisation et aux mutations des activités postales : Belgique, Bulgarie, Espagne, France et Royaume-Uni - Bolduc, François (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Facteurs en Europe. Le syndicalisme face à la libéralisation et aux mutations des activités postales : Belgique, Bulgarie, Espagne, France et Royaume-Uni," edited by Paul Bouffartigue and Jean Vandewattyne.

Les attentes des cadres du secteur parapublic québécois à l’égard de leur représentation collective - Bolduc, François; Grenier, Jean-Noël (Relations industrielles / Industrial Relations, 2023)
La question de la représentation collective des cadres a été remise à l’ordre du jour récemment, à la suite de l’initiative de l’Association des cadres de la Société des casinos du Québec ainsi que de l’Association professionnelle des cadres de premier niveau d’Hydro-Québec, qui ont obtenu l’autorisation du Tribunal administratif du travail de se constituer en syndicats, malgré le statut de cadre de leurs membres. Cette décision, qui a été confirmée en février 2022 par la Cour d’appel du Québec, soulève de nombreux questionnements sur le futur de la représentation collective de cette catégorie de travailleurs. Cet article entend contribuer à la réflexion sur ce thème, en mettant en lumière les attentes qu’entretiennent les cadres du secteur parapublic québécois à propos de leurs associations représentatives et de leurs modes d’action. Pour ce faire, nous mobilisons des résultats provenant de deux recherches réalisées auprès de cadres du secteur de la santé et des services sociaux, membres de l’AGESSS, et du secteur de l’éducation, membres de l’AQCS. Ces cadres expriment leur accord face à d’éventuelles modifications de l’encadrement législatif de leurs relations de travail. Cela dit, ils ne manifestent pas pour autant une volonté de se syndiquer. Qui plus est, ils sont ambivalents quant à l’utilisation éventuelle de modes d’action revendicateurs. Nous posons l’hypothèse que ce rapport au syndicalisme est une affirmation identitaire, qui s’explique, entre autres, par la façon dont le Code du travail définit les acteurs des relations du travail.
Keywords: Représentation collective; association représentative; cadres; représentation des intérêts; secteur parapublic québécois

Petite histoire politique des banlieues populaires - Bourdages, Jade; Gilbert, Izara (Labour / Le Travail, 2023)
The article reviews the book, "Petite histoire politique des banlieues populaires," by Hacène Belmessous.

Dynamiques de l’organisation collective des coursiers et des chauffeurs en Belgique. Histoires parallèles et rapprochement ambigus - Brodersen, Meike; Dufresne, Anne; Joukovsky, Anastasia; Vitali, Zéphyr (Relations industrielles / Industrial Relations, 2023)
Cet article met en lumière la façon dont les actions et revendications des collectifs de coursiers et de chauffeurs de plateforme bruxellois s’articulent avec les stratégies syndicales et les modèles de régulation de l’économie de plateforme, à l’échelle nationale et internationale, ainsi que les différentes lignes de tension que cette articulation suscite. En Belgique, les mobilisations dans la livraison et dans le transport de personnes par plateforme numérique s’inscrivaient jusqu’il y a peu dans des dynamiques sous-sectorielles distinctes, mais des développements législatifs récents et un accord de partenariat syndical ont créé les conditions de rapprochement des collectifs de ces deux sous-secteurs autour d’objets de contestation communs, sans pour autant aligner leurs intérêts sur le plan du statut d’emploi.
Keywords: Deliveroo; Platform worker; Travailleur de plateforme; Uber; accord de partenariat; collectifs de travailleurs; organisations syndicales; partnership agreement; presumption of employment; présomption de salariat; trade union organisations; worker collectives

Les plateformes de travail numériques. Polygraphie d’un nouveau modèle organisationnel. - Brugière, Fabien (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Les plateformes de travail numériques. Polygraphie d’un nouveau modèle organisationnel." edited by Mircea Vultur.

Dynamics of Mobilizing and Unionizing Mobility Platform Workers. A Cross-Country, Cross-Industry Analysis - Brugière, Fabien; Kesselman, Donna; Vandewattyne, Jean (Relations industrielles / Industrial Relations, 2023)
...The articles in this special issue attempt to account for these emerging dynamics of workers struggle in platform capitalism through a comparative analysis of the relations that impel autonomous groupings and other protest initiatives towards more structured collective representation and unionization.

Dynamiques de mobilisation et de syndicalisation des travailleurs de plateforme. Approche comparative transnationale et intersectorielle au sein des activités de mobilité - Brugière, Fabien; Kesselman, Donna; Vandewattyne, Jean (Relations industrielles / Industrial Relations, 2023)
...L’ambition de ce numéro thématique est ainsi de rendre compte des dynamiques de lutte et de syndicalisation au sein du capitalisme de plateforme, à travers une analyse comparative des rapports qui unissent ou non travailleurs, collectifs et autres structures de contestation avec les organisations syndicales.

Deindustrialization, Gender, and Working-Class Militancy in Saint-Henri, Montréal - Burrill, Fred (Labour / Le Travail, 2023)
Tracing the history of gendered working-class responses to deindustrialization in the Montréal neighbourhood of Saint-Henri reveals that many of the local political initiatives of the 1960s and 1970s were connected to longer-term working-class efforts to navigate shifting patterns of capital accumulation extending back to the 1940s. The gendered tradition of territory-based organizing in this community encouraged women workers’ shop-floor militancy and was foundational for new forms of local political advocacy around issues like health care and housing. In deindustrialization’s moment, the concerns of a precariously employed, feminized working-class population spurred a crossover of industrial struggle with survival-focused reproductive labour issues, centred around a grassroots organization called the popir (Projet d’organisation populaire, d’information, et de regroupement). This pattern of gendered working-class militancy and solidarity persisted throughout the 1980s and shaped resistance to Saint-Henri’s subsequent gentrification at the turn of the new millennium.
Keywords: Saint-Henri; deindustrialization; gender; gentrification; housing; women; working class

Les syndicats face aux restructurations initiées par les dirigeants d’entreprises : processus d’acquisition d’une capacité d’influence - Camara, Mactar (Relations industrielles / Industrial Relations, 2023)
Cet article part du constat que les travaux s’intéressant à la variation des réponses syndicales aux changements initiés par les dirigeants d’entreprises, en ne se concentrant que sur les différences entre syndicats et en analysant les réponses de chaque syndicat à l’aune d’un seul des différents types de réponse possibles, présentent une vision relativement statique de l’activité syndicale en période de changement. En s’appuyant sur les notions de pouvoir discursif/narratif (Geelan, 2022 ; Schmalz et al., 2018 ; Lévesque & Murray, 2013), de cadres de l’action collective (Snow & Benford, 1988) et de ressources de pouvoir (Lévesque et Murray, 2010), l’article cherche à voir comment l’intersyndicale de NRTV, une entreprise audiovisuelle française, confrontée au pouvoir formel des dirigeants du Groupe pour orchestrer leur projet de restructurations avec suppressions d’effectifs, a réussi à modifier les structures de pouvoir (Kaplan, 2008) et à peser dans les négociations. L’analyse du discours de l’intersyndicale, entre l’annonce du projet de restructuration et la fin des négociations, nous a permis d’identifier quatre stratégies de cadrage utilisées pour faire face aux significations fournies par les dirigeants du Groupe (la réfutation, l’euphémisation, le dévoilement et le recadrage). Ce positionnement discursif, combiné à l’utilisation d’une stratégie de diffusion des cadres interprétatifs et d’action aussi bien informationnelle qu’interprétative (Demers, 1996), lui a permis de mobiliser ses soutiens internes et externes autour et même au-delà des actions qu’elle a menées et d’exercer une influence sur le processus et les résultats du changement.
Keywords: analyse de discours; cadres de l’action collective; collective action frames; construction sociale du changement; discourse analysis; discursive power; pouvoir discursif; power resources; ressources de pouvoir; réponses syndicales aux restructurations d’entreprises; social construction of change; union responses to restructuring

Doctrine de prévention et activité de service : analyse des points de dissonance entre le dispositif de prévention et l’activité de médiation sociale - Chambel, Alexis; Pueyo, Valérie (Relations industrielles / Industrial Relations, 2023)
Les cadres de pensée et d’action qui structurent la prévention des risques professionnels forment aujourd’hui un dispositif au sens de Foucault. Ce dispositif, qualifié de « doctrine de prévention », s’est construit en référence aux classes de situations industrielles et se retrouve aujourd’hui remis en question par les activités de service. À partir d’une analyse ergonomique du travail et de la conduite de projet de prévention dans une structure de médiation sociale, cet article cible un point spécifique de la doctrine qui s’inscrit en décalage avec l’activité des médiatrices : la subordination. En effet, le lien qui s’établit entre subordination et prévention amène à penser cette dernière dans un périmètre et sur un modèle du pouvoir éloignés de l’activité réelle des travailleuses. Cet article fournit ainsi des connaissances spécifiques sur l’écart entre la doctrine de prévention et les activités de service, mais ouvre également des perspectives de recherche au travers de la conceptualisation de la prévention en tant que dispositif.
Keywords: Doctrine de prévention; activité de service; classes de situations servicielles; dispositif; pouvoir; projet de prévention; subordination

Emerging Patterns of Collective Action in India’s Platform Economy: A Study of Drivers and Delivery Workers - Chintala, Swati Reddy (Relations industrielles / Industrial Relations, 2023)
Studying collective action in the platform economy against the backdrop of the informal economy in India, I make two arguments that show how work organization in the platform economy enables collective action and distinguishes it from the informal sector. First, I argue that platform work organization through algorithmic work allocation, high employer visibility and algorithmic rather than direct managerial control makes collective action possible. In the informal economy, layers of middlemen often obscure the employment relationship by denying workers a clear contender and the opportunity to develop relationships of solidarity. Second, platform workers address their demands to two targets: the platform company and the state. Informal worker unions have no single, identifiable employer and traditionally confine their demands to the state.
Keywords: India; algorithmic control; collective action; informal economy; mobilization; platform economy; union; work

Les défis de la mobilisation collective et de l’organisation politique des travailleurs de plateformes au Brésil : une approche ergologique - Christo, Cirlene; Oliveira, Simone; Alvarez, Denise; Masson, Letícia; Lacomblez, Marianne (Relations industrielles / Industrial Relations, 2023)
Dans le cadre de la plateformisation du travail, l'article est consacré aux défis d’une construction de l'action collective de livreurs et de chauffeurs de centres urbains au Brésil. Le contexte socio-politique et économique de dépendance au sein du système capitaliste dans lequel agit ce groupe social, en interaction avec la rationalité néolibérale, contribue à expliquer les difficultés d'organisation syndicale de ces travailleurs. L’échantillon d’enquête réunit des dirigeants, des animateurs et des membres de collectifs en quête de meilleures rémunérations et conditions de travail, ainsi que d’alternatives aux plateformes marchandes. Ils intègrent deux associations, deux collectifs autogérés et un réseau autonome de travailleurs. En se fondant sur l'analyse des entretiens réunis, des hypothèses sont avancées concernant ces formes alternatives d'organisation, de représentation et de mobilisation, en tenant compte de la composition hétérogène de ces entités collectives.
Keywords: Brésil; digitalisation; ergologie; néolibéralisme; organisation syndicale; précarisation du travail; travail de plateforme

Assessing MSDs before Introduction of a Cobot: Psychosocial Aspects and Employee’s Subjective Experience - Cippelletti, Emma; Azouaghe, Soufian; Pellier, Damien; Landry, Aurélie (Relations industrielles / Industrial Relations, 2023)
Musculoskeletal disorders (MSDs) are one of the main causes of work disability (EU-OSHA, 2019; WHO, 2019). Several solutions, including the cobotic system (EUROGIP, 2017), have been put forward to improve unhealthy working conditions and prevent MSDs. We sought to identify the MSD risk factors of workers on a screen-printed glass production line prior to introduction of a cobot. We used a mixed data collection technique: video observations and assessment of MSD risk factors by expert ergonomists, and then self-confrontation interviews with six production-line operators and subjective perception of risk factors. The two types of assessment (by experts and by operators) showed that the most demanding risk factors were physical (e.g., work posture) and psychosocial (e.g., mental workload). Certain risk factors were viewed differently by the experts and the operators. One question remains: How can a cobot make work more meaningful for operators?
Keywords: Cobot; Industry 4.0; MSDs; Meaning of work; Subjective experience

Love’s Next Meeting: The Forgotten History of Homosexuality and the Left in American Culture - Cleves, Rachel Hope (Labour / Le Travail, 2023)
The article reviews the book, "Love’s Next Meeting: The Forgotten History of Homosexuality and the Left in American Culture," by Aaron S. Lecklider.

Les visages de l'État social, Assistantes sociales et familles populaires durant l'entre-deux-guerres by Lola Zappi (review) - Courtemanche, Andréanne (Labour / Le Travail, 2023)
The article reviews the book, "Les visages de l'État social, Assistantes sociales et familles populaires durant l'entre-deux-guerres," by Lola Zappi.

Democracy at Work. Contract, Status and Post-Industrial Justice - Coutu, Michel (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Democracy at Work. Contract, Status and Post-Industrial Justice," by Ruth Dukes and Wolfgang Streeck.

Droit du travail et relations industrielles : Vers une refondation? - Coutu, Michel; Dukes, Ruth; Murray, Gregor (Relations industrielles / Industrial Relations, 2023)
Cet article explore les voies du renouvellement de l'étude des relations industrielles et du droit du travail. À travers un examen historique comparatif de ces deux domaines d’études, il examine leurs racines et héritages communs ainsi qu'une série d'initiatives de renouvellement. Il est soutenu que les deux domaines doivent se réapproprier des valeurs fondamentales : la reconnaissance de l'inégalité fondamentale des parties à la relation de travail et la reconnaissance de la nécessité de compenser cette inégalité par des processus collectifs. Les germes de ce renouveau sont identifiés à la fois dans le droit du travail et dans les relations industrielles. Leur avenir réside dans l'émergence d'un champ d’études intégré du travail et de l'emploi et dans le rôle et l'avenir du travail en tant que vecteur de démocratie.
Keywords: démocratie au travail; l’avenir du travail; relations industrielles; renouveau du champ d’études; régulation du travail; sociologie du droit du travail

Labour Law and Industrial Relations: Toward Renewal? - Coutu, Michel; Dukes, Ruth; Murray, Gregor (Relations industrielles / Industrial Relations, 2023)
This article explores paths for the renewal of the study of industrial relations and labour law. Through a comparative historical review of these two fields of study, it examines their common roots and legacies and a range of renewal initiatives. It is argued that both fields need to reappropriate core values: recognition of the fundamental inequality of the parties to the employment relationship; and recognition of the need to compensate for this inequality through collective processes. The seeds of this renewal are identified in both labour law and industrial relations. Their future lies in the emergence of an integrated field of study of work and employment and in the role and future of work as a vector of democracy.
Keywords: citizenship at work; democracy at work; future of work; industrial relations; regulation of work; renewal of field of study; sociology of labour law

Interprovincial Unionization and the Environment - Das, Anupam; Hudson, Ian; Hudson, Mark (Labour / Le Travail, 2023)
The relationship between labour movements and the environment has been the subject of considerable debate but little empirical research. Using panel data for Canadian provinces between 2001 and 2019, this article investigates the relationship between unionization rates and two measures of environmental quality: greenhouse gas emissions and total particulate matter pollution. We find that higher unionization rates are associated with lower emissions for both these measures. This finding suggests that stronger labour organizations do not lead to detrimental environmental outcomes.
Keywords: Canada; climat; climate; environment; environnement; pollution; syndicalisation; unionization

Acceptable and Necessary Treasons: The Revolutionary Prophecies of Noel Ignatiev - Davis, Dylan; King, Patrick (Labour / Le Travail, 2023)
The article reviews and comments on two books by American author and historian Noel lgnatiev (1940-2019): "Treason to Whiteness is Loyalty to Humanity," edited by Geert Dhondt, Zhandarka Kurt, and Jarrod Shanahan, and "Acceptable Men: Life in the Largest Steel Mill in the World."

Living to Work (from Home): Overwork, Remote Work, and Gendered Dual Devotion to Work and Family - de Laat, Kim (Work and Occupations, 2023)
Contemporary North American work culture is characterized by experts as one of overwork. Throughout much of the previous century, many parents devoted themselves either to their careers, or to their families. These “competing devotions” served as a cultural model for making sense of the world and alleviated the tension between overwork and family life. Data from interviews with 84 IT workers are used to examine whether devotion to work and family is still experienced as oppositional for working parents. I find that interviewees report feeling devoted both to their families and their careers, which I refer to as dual devotion. Such espousals of dual devotion are facilitated by the use of flexible work policies—remote work and flextime—which enable those with dual devotions to accomplish work–life integration. However, whereas men perceive remote work as allowing them to dedicate more time to childcare, women perceive it as allowing them to dedicate more time to work. These findings advance our understanding of the relationship between gender inequality and the experiential dimensions of work and family time: the practices that enable dual devotions, in particular remote work, help parents maintain an orientation to time that makes overwork more palatable. In either case, workplaces win since women are working long hours and men are not sacrificing paid work hours to take on more childcare or housework.

Centralized Bodies of Collective Representation in the Fragmented Company: A Power Resource? - Devetter, François-Xavier; Geymond, Maé; Perez, Coralie; Perraudin, Corinne; Thèvenot, Nadine; Valentin, Julie (Relations industrielles / Industrial Relations, 2023)
Could “centralized” bodies of collective representation constitute a power resource for employees in contemporary fragmented work organizations? Referring to the particular features of the institutional framework in France, this article links the theory of power resources to the concept of institutional toying to show that the power resources of managers allow them to make use of institutional shortcomings that limit the scope of these bodies as power resources for employees. The article draws on the REPONSE 2017 (DARES) survey, which sought to quantify “fragmented” organizations and their collective representation bodies. Six case studies of fragmented companies are also used to illustrate the diversity of institutional toying strategies employed by managers.
Keywords: Outsourcing; centralized bodies; collective representation; management strategy; power resources; subcontracting; subsidiaries

Les instances centralisées de représentation collective dans l’entreprise éclatée : une ressource de pouvoir? - Devetter, François-Xavier; Geymond, Maé; Perez, Coralie; Perraudin, Corinne; Thèvenot, Nadine; Valentin, Julie (Relations industrielles / Industrial Relations, 2023)
Les instances « centralisées » de représentation collective pourraient-elles constituer une ressource de pouvoir pour les salariés dans les organisations de travail fragmentées contemporaines? En se référant aux spécificités du cadre institutionnel français, cet article articule la théorie des ressources de pouvoir au concept de modelage institutionnel pour faire apparaître que les ressources de pouvoir des directions leur permettent de s’appuyer sur des lacunes institutionnelles limitant la portée de ces instances comme ressources de pouvoir pour les salariés. Il utilise l’enquête REPONSE 2017 (DARES) pour quantifier les entreprises « éclatées » ainsi que leurs instances de représentation collective. Six monographies d’entreprises éclatées sont également mobilisées pour illustrer la diversité des stratégies de modelage institutionnel des directions.
Keywords: Sous-traitance; filialisation; instances centralisées; représentation collective; ressources de pouvoir; stratégie patronale

"Our Relations… The Mixed Bloods": Indigenous Transformation and Dispossession in the Western Great Lakes - Devine, Heather (Labour / Le Travail, 2023)
The article reviews the book, "'Our Relations… The Mixed Bloods': Indigenous Transformation and Dispossession in the Western Great Lakes," by Larry Nesper.

Différences irréconciliables : conceptualisation du conflit en relations industrielles et en comportement organisationnel - Dickey, Todd (Relations industrielles / Industrial Relations, 2023)
Dans les dernières décennies, les spécialistes en relations industrielles (RI) n’ont cessé de préconiser une meilleure intégration de leurs théories et de leurs recherches empiriques sur le conflit à celles de leur discipline voisine, le comportement organisationnel (CO). La réalisation d’un tel objectif s’est néanmoins révélée un défi constant. Cet article offre une nouvelle perspective sur la quête de cette intégration par l’entremise d’une catégorisation des normes conceptuelles distinctes et dissemblables du conflit en RI et en CO, laquelle amène à conclure que les conceptualisations du conflit dans ces deux disciplines reposent sur des logiques inconciliables. Toutefois, même si ces logiques divergentes rendent impossible une conceptualisation unifiée du conflit, une meilleure compréhension de leur caractère inconciliable pourrait mener à un renforcement du dialogue et, à terme, à une discussion fructueuse entre les chercheurs en RI et en CO.
Keywords: Théorie des organisations; comportement organisationnel; conflit organisationnel; théorie des relations industrielles

Irreconcilable Differences: Conceptualizing Conflict in Industrial Relations and Organizational Behaviour - Dickey, Todd (Relations industrielles / Industrial Relations, 2023)
Over the past several decades, industrial relations (IR) scholars have consistently advocated for better integration of their conflict theory and empirical research with that of the neighbouring discipline of organizational behaviour (OB). Achievement of such a goal has nonetheless been a continuing challenge. Offering a novel perspective on the quest for integration, this paper categorizes the distinct and dissimilar conceptual norms of conflict in IR and OB, concluding that conceptualizations of conflict in the two disciplines are built upon irreconcilable logics. Although a unified conceptualization of conflict across these differing logics is not possible, a better understanding of their irreconcilability could facilitate a more robust and ultimately fruitful dialogue among IR and OB researchers.
Keywords: industrial relations theory; organizational behaviour; organizational conflict; organizational theory

Perceptions de justice et santé au travail. L’organisation à l’épreuve. Collection Inégalité et justice sociale - Dompierre, Johanne (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Perceptions de justice et santé au travail. L’organisation à l’épreuve. Collection Inégalité et justice sociale," edited by Stéphane Moulin.

Unsettling the Great White North. Black Canadian History - Dumais, Samia (Labour / Le Travail, 2023)
The article reviews the book, "Unsettling the Great White North. Black Canadian History," by Funké Aladejebi and Michele A. Johnson.

Blanc de plomb. Histoire d’un poison légal - Fahrni, Magda (Labour / Le Travail, 2023)
The article reviews the book, "Blanc de plomb. Histoire d’un poison légal," by Judith Rainhorn.

A Just Transition for Labour: The Challenges of Moves to a Circular Economy - Fairbrother, Peter; Banks, Marcus (Relations industrielles / Industrial Relations, 2023)
Proposals for a just transition for labour have been largely restricted to debates about transitions in coal regions. Yet a just transition for labour should apply to all industries. Alongside these debates, planning guidelines are in place to encourage the adoption of circular economy practices to address questions relating to material sustainability, especially in the context of the encroaching climate crisis. Surprisingly, few people have considered the implications of such changes for work and employment relationships. Unless a just transition is pursued, current inequalities in the housing construction industry are likely to intensify and remain embedded. The argument is that moves toward a circular economy in Australian housing construction require a just transition for the workforce. Such a transition must be planned and inclusive.
Keywords: Construction de Bâtiment; Transition Juste; Travail Décent; building construction; circular economy; decent work; just transition; Économie Circulaire

From Printing to Streaming: Cultural Production under Capitalism - Fauteux, Brian (Labour / Le Travail, 2023)
The article reviews the book, "From Printing to Streaming: Cultural Production inder Capitalism," by Michael Chanan.

Construire l'économie postcapitaliste - Folco, Jonathan Durand (Labour / Le Travail, 2023)
The article reviews the book, "Construire l'économie postcapitaliste," by Audrey Laurin Lamothe, Frédéric Legault, and Simon Tremblay-Pepin.

La négociation collective du secteur de l’éducation : quel avenir pour le Front commun? - Fortin-Bergeron, Chloé; Gagné, Diane (Relations industrielles / Industrial Relations, 2023)
Cette étude s’intéresse à la capacité des organisations syndicales à améliorer les conditions de travail de leurs membres en contexte d’austérité économique. Pour ce faire, nous nous intéressons au cas de la négociation 2014-2015 au sein du secteur public québécois et plus particulièrement à la négociation dans le secteur de l’Éducation primaire-secondaire. Proposant une approche d’analyse multiniveau et multidimensionnelle et mobilisant un devis qualitatif, nous souhaitons engager une réflexion sur la capacité des syndicats du secteur de l’éducation à répondre à la précarité dans ce secteur. La position que nous avançons dans cet article est que les syndicats n’ont pas été en mesure de saisir certaines opportunités leur permettant de renforcer leur pouvoir de force aux tables de négociation. Nos principaux résultats nous amènent à faire le constat que les structures centralisées n’ont pas bien servi le front commun lors de la négociation de 2015; la négociation inter et intraorganisationnelle s’est avérée difficile et peu efficace compte tenu des multiples réalités et enjeux et de la stratégie fortement centralisée du gouvernement. Nous avons aussi constaté que la précarité vécue et perçue par les membres du secteur de l’éducation est très spécifique au contexte et aux caractéristiques de l’emploi; une spécificité qui semble plus difficile à faire reconnaitre au sein de structures centralisées. Partant de la thèse du « syndicalisme fantôme » proposé par Desbiens (2020) et du pragmatisme syndical de Lemieux (2021), nous engageons une réflexion et proposons des pistes d’action de manière à favoriser un rapprochement entre les différents paliers d’action syndicale et d’arrimer plus solidement la praxis syndicale aux attentes des membres.
Keywords: Austérité économique; Capacités syndicales; Négociations secteur public; Précarité; Secteur de l’éducation; Structures de négociation centralisées

Union Donations to Community Organisations and the Dampening Effect of Government Legislation: The Case of Bill 32 in Alberta, Canada - Foster, Jason; Simpson, David (Labour and Industry, 2023)
Unions in North America have a long history of financial support for charities, non-profits and other community-based organisations. However, very little research has been conducted into how much, to whom and why this financial support is provided. This article reports on a survey examining the financial donation patterns of unions in the Canadian province of Alberta. Alberta is chosen as the jurisdiction for the study as the provincial government recently enacted legislation (commonly referred to as Bill 32) that may force unions to reduce community-based donations, which would negatively impact those organisations and interfere with a core union function. The survey also examines how union financial support changes due to the implementation of this legislation. The study finds that a small but not insignificant percentage of union expenditures are devoted to community giving and that unions tend to donate to a narrow range of causes and organisations. It also finds that union responses to donation-dampening legislation were mixed, in part due to the politically controversial nature of the legislation.
Keywords: Trade unions; community organisation donations; government legislation; union finances

From Unwoven Societal Relationships to a Broad-Based Movement? Union Power in Societal Networks in Quebec (Canada) - Frangi, Lorenzo; Masi, Anthony C; Poirier, Bénédicte (Work, Employment and Society, 2023)
Power resources are embedded in societal ties. Using qualitative network analysis, our fieldwork in Quebec (Canada), based on 30 interviews and three focus groups, explored union-societal ties, their resource properties and the extent to which unions weave them into a network. We identified five different types of union-societal ties: instrumental, civil society organizations, identity-based, satellite and fishing line. These ties were mostly unwoven. Analysis of networking provides insights into how unions frame issues, identify grassroots leaders and leverage societal power resources in broad-based movements.

Managers et syndicats : duel ou duo ? - Fronty, Juliette (Relations industrielles / Industrial Relations, 2023)
Dans un contexte d’affaiblissement du dialogue social en général et de la légitimité des syndicats en particulier, nous proposons dans cet article de renouveler notre regard sur le binôme managers et syndicats à travers un changement de perspective. Dans le cadre d’une recherche qualitative approfondie menée au sein de l’industrie aéronautique française, nous nous sommes intéressée au dialogue informel quotidien entre les middle-managers et délégués syndicaux à l’échelle de l’atelier (Kochan, Katz et McKersie, 1994). Nous avons cherché à identifier la nature et les conditions du dialogue entre managers et syndicats dans leur activité quotidienne. Pour ancrer ce changement de perspective, nous utiliserons le concept de dialogue relationnel (Cunliffe et Eriksen, 2011) permettant de dépasser l’approche traditionnelle de dialogue social et pour en éprouver autrement l’effet. Nous montrerons alors que le dialogue relationnel, qui est basé sur une qualité relationnelle, une approche processuelle du dialogue et sa dimension polyphonique, permet aux middle-managers d’anticiper les tensions dans les équipes et d’améliorer leurs décisions managériales. Or, ce dialogue relationnel n’est pas perçu de manière positive par toute l’organisation, notamment les responsables des ressources humaines, qui tentent d’en réduire l’impact grâce à la mise en place d’outils de gestion empêchant les arbitrages plus informels issus du dialogue entre les managers et les syndicats. S’inscrivant dans l’évolution récente des recherches en RI s’enrichissant de cadres conceptuels venant des organizations studies, cet article contribue à tester le concept de dialogue relationnel non pas entre le manager et ses collaborateurs, mais avec des responsables syndicaux. Nous avons ainsi pu identifier des conditions organisationnelles de ce dialogue, ce qui n’avait pas encore été fait. En effet miroir, l’application du concept de dialogue relationnel dans une situation de relations professionnelles permet d’enrichir l’approche pluraliste en soulignant à la fois ses potentialités et l’importance des conditions nécessaires à ce type de dialogue.
Keywords: dialogue relationnel; managers intermédiaires; middle managers; pluralism; pluralisme; relational dialogue; syndicats; trade unions

The Origin and Dynamics of Inequality: Sex, Politics and Ideology - Gould, Anthony (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "The Origin and Dynamics of Inequality: Sex, Politics and Ideology," by Jon Wisman.

Qu’ont à se dire l’économie du travail et les relations industrielles ? - Gunderson, Morley (Relations industrielles / Industrial Relations, 2023)
Une meilleure pollinisation croisée entre l’économie du travail et les relations industrielles conduirait à des gains mutuels. Le présent article s’articule autour de critiques courantes de l’économie du travail qui sont illustrées par des exemples tirés des relations industrielles. Ces critiques, ainsi que leurs principes sous-jacents, expliquent souvent d’importants concepts des relations industrielles et apportent par le fait- même des connaissances susceptibles d’enrichir les réflexions en économie du travail. L’intention de cet article est d’avoir un regard prospectif pour faire avancer la réflexion théorique et empirique sur les aspects actuels et futurs du travail et de l’emploi.
Keywords: gains mutuels; relations industrielles; Économie du travail

What Do Labour Economics and Industrial Relations Have to Say to Each Other? - Gunderson, Morley (Relations industrielles / Industrial Relations, 2023)
Mutual gains can be made through greater cross-pollination between labour economics and industrial relations. The paper is organized around common criticisms of labour economics, with examples from industrial relations. Such criticisms, and their underlying principles, often explain important concepts in industrial relations, which can provide insights that may enhance labour economics. The intent here is to apply a forward-looking lens to advance theoretical and empirical reflection on current and future aspects of work and employment.
Keywords: labour economics; mutual gains with industrial relations

Making and Breaking Settler Space: Five Centuries of Colonization in North America - Haggarty, Liam (Labour / Le Travail, 2023)
The article reviews the book, "Making and Breaking Settler Space: Five Centuries of Colonization in North America," by Adam J. Barker.

“Vulnerable Workers” and Third Way Governance: Shifting Subjects of Regulation in Ontario’s Employment Standard Enforcement Regime - Hall, Alan; Grundy, John; Vosko, Leah F.; Hall, Rebecca (Journal of Law and Political Economy, 2023)
This article traces the definition and treatment of “vulnerable workers” within the province of Ontario’s regulation of employment standards over a fourteen-year period. An examination of the government’s discourse and its enforcement and legislative history reveals significant shifts and inconsistencies between the government’s claims and its enforcement practices. These shifts and inconsistencies are understood within a political economic analysis of “Third Way” employment policies, competing liberal ideologies, shifting political-economic conditions and institutional legacies. The analysis contributes to a cross-national literature exploring the inadequacies of employment standards enforcement in liberal market economies while at the same time identifying opportunities for change within the different “varieties of liberalism” exhibited within Third Way regimes.

The Radical Origins of the Deindustrialization Thesis: From Dependency to Capital Flight and Community Abandonment - High, Steven C. (Labour / Le Travail, 2023)
Deindustrialization became a pressing political issue and an object of research almost simultaneously in North America. This article inquires into the intellectual origins and radical roots of the deindustrialization thesis in Canada and the United States. Though the two countries share much in common, their distinctive formulations of the deindustrial problem in the 1970s and 1980s reflected key economic and political differences between them. Radical political economists in Canada and the United States turned to dependency theory and capital flight, respectively, in their theorization of deindustrialization. Barry Bluestone and Bennett Harrison’s 1982 book, The Deindustrialization of America, in particular, is a founding text for the burgeoning field of deindustrialization studies. We can learn much from re-engaging with this early scholarship. In doing so, however, we need to bridge the continuing analytical divide between micro-level labour histories of working-class communities and macro-level studies of political economy and the international division of labour.
Keywords: capital mobility; deindustrialization; dependency; international division of labour; political economy; staples

Working for Respect: Community and Conflict at Walmart - Hocquelet, Mathieu (Labour / Le Travail, 2023)
The article reviews the book, "Working for Respect: Community and Conflict at Walmart," by Adam Reich and Peter Bearman.

Syndiquer sans mobiliser : la plateformisation du travail et ses conséquences sur le syndicalisme chinois - Huang, Ke (Relations industrielles / Industrial Relations, 2023)
Comment les syndicats chinois réagissent-ils à la plateformisation du travail et à la résistance des travailleurs des plateformes ? Centré sur les livreurs de repas, cet article examine les défis que le travail de plateforme pose à la Fédération nationale des syndicats de Chine (Zhonghua quanguo zonggonghui中华全国总工会), la seule organisation syndicale légale en Chine, et la manière dont, dans un premier temps, les livreurs se sont mis en lutte sans l’intervention des syndicats. Dans un deuxième temps, répondant aux injonctions des autorités politiques, la FNSC a cherché à syndiquer les livreurs en développant de nouveaux modes d’organisation. Parallèlement, elle a développé une offre de service à destination de ces travailleurs. Ce n’est que tout récemment qu’elle s’est impliquée dans la négociation de conventions collectives portant sur les conditions d’emploi et de travail des livreurs. Même si le manque de recul ne permet pas de saisir la portée réelle de ces négociations, elle interpelle cependant par rapport à la réalité du syndicalisme en Chine.
Keywords: ACFTU; China; Chine; FNSC; Food delivery workers; Livreurs de repas; auto-organisation; mobilisation; mobilization; plateforme; platforms; self-organization; syndicats; trade unions

The Heart of Toronto: Corporate Power, Civic Activism, and the Remaking of Downtown Yonge Street - Hyde, Zachary (Labour / Le Travail, 2023)
The article reviews the book, "The Heart of Toronto: Corporate Power, Civic Activism, and the Remaking of Downtown Yonge Street," by Daniel Ross.

Transformed or Transferred? How Workers Perceive Managerial Control over Home Telework. Some Insights from an Italian Case - Iannuzzi, Francesco Eugenio; Campolongo, Francesco (Relations industrielles / Industrial Relations, 2023)
We examined how home-based teleworkers perceived managerial control in an Italian context in order to gain insight into some of the organizational changes brought on by the COVID-19 pandemic. Drawing on studies of changes to managerial control over the past few decades, we show how workers have experienced the reconfiguration and hybridization of control practices and methods in home telework. Our results cast doubt on the widely held belief that telework is revolutionizing managerial control and work procedures. Organizational and power dynamics at work are key to determining how telework affects employee experiences.
Keywords: contrôle managérial; expériences des travailleurs; managerial control; pandemic; pandémie; telework; télétravail; worker’s experiences

Introduction du numéro spécial sur la contribution des relations industrielles à la compréhension de l’avenir du travail et de l’emploi - Jalette, Patrice; Pohler, Dionne (Relations industrielles / Industrial Relations, 2023)
Pour célébrer le 60e anniversaire de l’Association canadienne des relations industrielles (ACRI), Relations industrielles-Industrial Relations (RI-IR) et l’ACRI ont convenu de publier un numéro spécial afin de faire progresser et de consolider les connaissances dans notre domaine. Depuis plus d’un siècle en Amérique du Nord, les chercheurs et les praticiens des relations industrielles étudient les problèmes liés au travail et à l’emploi, qui se perpétuent dans le cadre des modèles de production capitalistes, mais qui deviennent de plus en plus diversifiés et complexes. Par exemple, alors que le travail précaire, la santé et la sécurité au travail et les changements technologiques ont toujours posé des défis aux travailleurs, la pandémie mondiale de COVID-19 a montré que nous n’avons pas fait tout ce que nous pensions pour créer des systèmes d’emploi ou des politiques du travail qui facilitent l’équilibre entre la vie professionnelle et la vie privée, protègent les revenus des travailleurs contre les risques sociaux, permettent d’atteindre l’équité en matière d’emploi, retiennent les personnes et les compétences nécessaires au bon fonctionnement des organisations et respectent l’exercice des droits fondamentaux par les travailleurs. De plus en plus, les praticiens doivent faire face à ce que certains appellent une « polycrise », c’est-à-dire plusieurs crises simultanées (par exemple, le vieillissement de la population, l’inflation, l’évolution des préférences des travailleurs, le travail à distance et/ou le retour au travail en personne, les changements démographiques générationnels). Ces crises se combinent et s’exacerbent les unes les autres, rendant ainsi les problèmes classiques de main-d’oeuvre plus imprévisibles et plus complexes. --Introduction

Introduction to the Special Issue on the Contribution of Industrial Relations to Understanding the Future of Work and Employment - Jalette, Patrice; Pohler, Dionne (Relations industrielles / Industrial Relations, 2023)
To commemorate the Canadian Industrial Relations Association’s (CIRA-ACRI) 60th anniversary, Relations industrielles-Industrial Relations (RI-IR) and CIRA have agreed to publish a special issue to advance and consolidate knowledge in our field. For more than a century in North America, industrial relations scholars and practitioners have been studying work and employment problems, which remain age-old under capitalist models of production but are becoming more diverse and complex. For instance, while precarious work, occupational health and safety and technological change have always challenged workers, the global COVID-19 pandemic has shown that we have not come as far as we think in creating employment systems or labour policies that facilitate work-life balance, protect worker incomes against social risks, achieve employment equity, retain the people and skills required for effective operation of organizations and respect workers’ exercise of fundamental rights. More and more, practitioners must deal with what some call a “polycrisis”—several crises happening at once (e.g., population aging, inflation, changing worker preferences, remote work and/or a return to face-to-face work, generational demographic shifts). These crises combine with and exacerbate each other, thus making classic labour problems more unpredictable and complex. --Introduction

Under the Iron Heel: The Wobblies and the Capitalist War on Radical Workers - Kealey, Gregory S. (Labour / Le Travail, 2023)
The article reviews the book, "Under the Iron Heel: The Wobblies and the Capitalist War on Radical Workers," by Ahmed White.

Medicare’s Histories: Origins, Omissions, and Opportunities in Canada - Kealey, Linda (Labour / Le Travail, 2023)
The article reviews the book, "Medicare’s Histories: Origins, Omissions, and Opportunities in Canada," edited by Esyllt W. Jones, James Hanley, and Delia Gavrus.

Superstack Nostalgia: Miners and Industrial Heritage in Sudbury, Ontario - King, Adam D. K. (Labour / Le Travail, 2023)
The growth of industrial tourism and heritage has both fascinated and frustrated scholars of deindustrialization. Frequently, workers and class conflict are obscured in or expunged from the official narratives of industrial heritage. This article makes an original contribution to research on deindustrialization and industrial heritage through fieldwork in Sudbury, Ontario – a region that has seen a decades-long process of industrial restructuring. The article draws on 26 qualitative interviews with current and retired nickel miners and analyzes workers’ reflections on local mining history. It examines how workers understand the foreign takeover of the mines, job loss, and the transformation of Sudbury’s regional economy away from blue-collar industrial employment. The article then explores the growth of regional tourism based around the mining sector, looking particularly at Dynamic Earth, an attraction that teaches visitors about the history of nickel mining through guided tours of a closed mine. On the one hand, workers critique what they see as an obfuscation of class conflict in industrial heritage, while on the other hand, they experience these sites as confirmation of the historic contributions nickel miners have made to Sudbury and the surrounding region.
Keywords: deindustrialization; industrial heritage; industrial tourism; mining; nostalgia; working-class culture

The Origins and Application of the "Core of Indianness" in Indigenous Labour Relations: Returning to Four B Manufacturing v. United Garment Workers of America - King, Adam D. K.; Lyubchenko, Olena; Vosko, Leah F.; Noack, Andrea M.; Coburn, Veldon; Hall, Rebecca J. (Labour / Le Travail, 2023)
This article examines the history of, and legal precedent set by, Four B Manufacturing v. United Garment Workers of America, a 1980 Supreme Court of Canada case involving an Indigenous-owned manufacturing firm that resisted the efforts of its Indigenous and non-Indigenous workers to form a union on the Tyendinaga Mohawk Territory, a reserve in southeastern Ontario. The employer, Four B, contested the jurisdiction of the Ontario Labour Relations Board and argued, unsuccessfully, that as an "Indian enterprise," its own operations were a matter of federal jurisdiction. We return to the case of Four B for three interrelated reasons. First, we argue that Four B remains relevant because of the ways that the political economy of settler-colonial Canada continues to structure Indigenous enterprises, labour, and employment as ongoing sites of tension. Second, as the inaugural case dealing with the "core of Indianness" – a contested legal concept used by the courts to determine federal jurisdiction over Indigenous labour – this case both set the legal precedent and shaped the subsequent political terrain of Indigenous labour relations. Third, the issues addressed in Four B contextualize recent jurisdictional struggles over Indigenous enterprises, labour, and employment in what we term the "Indigenous public sector" – namely, health care, social services, and First Nations government administration. The article reviews the case history of Four B, setting this against the backdrop of deindustrialization in southeastern Ontario during the period, before tracing how the case influenced the juridical and political landscape of Indigenous labour relations. We close by considering the potential tensions between Indigenous self-determination and the exercise of collective bargaining rights by Indigenous workers.
Keywords: "core of Indianness"; Indigenous labour relations; colonialisme de peuplement; juridiction; jurisdiction; public-sector unionism; relations du travail autochtones; settler colonialism; syndicalisme dans le secteur public; « cœur de l'Indianité »

Querelle de Roberval - Lacroix, Michel (Labour / Le Travail, 2023)
The article reviews the book, "Querelle de Roberval," by Kevin Lambert.

“La Grève de la fierté”: Resisting Deindustrialization in Montréal’s Garment Industry, 1977–1983 - Laframboise, Lauren (Labour / Le Travail, 2023)
On 15 August 1983, 9,500 workers from the Montréal locals of the International Ladies’ Garment Workers’ Union went on strike for the first time in 43 years. The strike became known as “la grève de la fierté” and made clear that the women working in the city’s garment factories were taking a stand against the layoffs and closures prompted by industrial restructuring and deindustrialization. However, the strike’s success was limited, revealing the extent to which the structural inequities in the garment industry had calcified along gendered, classed, and ethnic lines. The union executive had grown increasingly distant from its rank-and-file, and it was immigrant women workers who were left to organize against the flurry of closures and the corresponding decline in their working conditions. The campaign leading up to the 1983 strike, organized by the Comité d’action des travailleurs du vêtement, articulated a series of demands for the improvement of workplace health and safety conditions, better benefits, and more representative union leadership. With original archival research and oral history interviews, I argue that the 1983 “grève de la fierté” illustrates how the historically entrenched gendered structure of labour relations shaped the pathways of deindustrialization in Montréal’s garment industry.
Keywords: Montréal; Québec; garment and textile industry; gendered labour; immigrant women; oral history; piecework; rank-and-file organizing; strike; trade liberalization

The Workers' Opposition in the Russian Communist Party: Documents, 1919–30 - Lalande, J.-Guy (Jean-Guy) (Labour / Le Travail, 2023)
The article reviews the book, "The Workers' Opposition in the Russian Communist Party: Documents, 1919–30," edited by Barbara C. Allen.

The South: Jim Crow and its Afterlives - Lichtenste[i]n, Alex (Labour / Le Travail, 2023)
The article reviews the book, "The South: Jim Crow and its Afterlives," by Adolph L. Reed, Jr., with a foreword by Barbara J. Fields.

“We Thought It Would Last Forever”: The Social Scars and Legacy Effects of Mine Closure at Nanisivik, Canada’s First High Arctic Mine - Lim, Tee Wern; Keeling, Arn; Satterfield, Terre (Labour / Le Travail, 2023)
Although mine closures are an inherent feature of extractive industry, they tend to receive less attention in the literature on deindustrialization than the closures of manufacturing and other heavy industries. Until recently, the settler-colonial context of hinterland mineral development and its impact on northern Indigenous lands and communities in Canada have also remained largely unexplored within this literature. Mineral development is historically associated with the introduction of a colonial-capitalist industrial modernity across Canada’s northern regions. Yet the boom-and-bust nature and ultimate ephemerality of mineral development has meant that resource-extractive regions have also been subject to intensive “cyclonic” periods of closure and deindustrialization. This article examines the experience of deindustrialization on the part of the Inuit community of Arctic Bay, who were largely “left behind” by the closure of Nanisivik, Canada’s first High Arctic mine. Through documentary sources and oral history interviews we illustrate how, for Arctic Bay Inuit who were engaged in the cyclonic economies of Nanisivik’s development and closure, there were myriad dimensions of social loss, displacement, and resentment associated with the failure of this industrial enterprise to deliver promised benefits to Inuit, beyond more commonly understood socioeconomic impacts such as job loss.
Keywords: Arctic; Indigenous communities; Inuit; Northern Canada; deindustrialization; industrial colonialism; mine closure; mining; ruination

Répression et dépossession politique - Livernois, Jonathan (Labour / Le Travail, 2023)
The article reviews the book, "1972. Répression et dépossession politique," by Olivier Ducharme.

Unionizing Delivery Platform Workers. The Spatiality of Struggles over Regulation and Deregulation of Delivery Work in Spain - López-García, Irene; Ribón-Seisdedos, Maria Antonia; Morales-Muñoz, Karol; Roca, Beltrán (Relations industrielles / Industrial Relations, 2023)
This article is about recent changes in the union strategy of Spanish platform workers. Using a socio-spatial approach to labour processes and disputes, we first describe the context of union organizing: how the business model of delivery platforms has evolved and how it is regulated in Spain. We then analyze the first initiatives to organize couriers in Spain. These initiatives can be classified under the heading of community unionism and have focused on specific spaces of union activism (state regulation and community support). Next, we explore how their newly won employee status has caused couriers to adopt more conventional forms of union organizing and focus on other spaces. Finally, we discuss the main challenges of reconciling union models with the working world of delivery platforms.
Keywords: community unionism; couriers; delivery platforms; industrial action; platform capitalism; platform workers; spatiality of labour; unions

Importing the Clairtone Sound: Political Economy, Regionalism, and Deindustrialization in Pictou County - MacKinnon, Lachlan (Labour / Le Travail, 2023)
Following the industrial crisis of the 1920s and the Great Depression in the 1930s, consecutive provincial governments in Nova Scotia turned their efforts toward state-led economic development. After the election of Robert Stanfield and the Tories in 1956, a wholesale industrial planning model was unveiled. Indeed, Stanfieldian economic policy in Nova Scotia was predicated upon the belief that direct state-led interventionism was necessary to offset regional inequity. State corporate entities, such as Industrial Estates Limited, and renewed interest in a state-driven industrial relations paradigm were central in the province’s efforts to revitalize its flagging economy and offset predicted decline in the Cape Breton coal and steel industries. This article examines the fate of the Clairtone Sound Corporation, one of Nova Scotia’s “new industries” that emerged out of these state-led development efforts. A case study of this Stellarton-based firm reveals how structural processes of deindustrialization produced crisis even within sectors that were completely distinct from the province’s cornerstone industries of coal and steel. This case includes a reflection on the class composition of the modernist state in Nova Scotia and represents a convergence of the historiographical focus on state-led industrial development in the Maritimes and recent literature found within deindustrialization studies.
Keywords: Atlantic Canada; Nova Scotia; coal; deindustrialization; economic planning; electronics; industrial development; regionalism

Deindustrialization in Canada: New Perspectives - MacKinnon, Lachlan; High, Steven C. (Labour / Le Travail, 2023)
Introduces the theme of deindustrialization in Canada including history, gender, regions, technology, and resistance Summarizes the various contributions to this special issue of the journal.

The Opportunity Trap: High-Skilled Workers, Indian Families, and the Failures of the Dependent Visa Program - Maghbouleh, Neda (Labour / Le Travail, 2023)
The article reviews the book, "The Opportunity Trap: High-Skilled Workers, Indian Families, and the Failures of the Dependent Visa Program," by Pallavi Banerjee.

Job Standardization and Employee Voice - Mao, Hsiao-Yen; Mao, Chueh-Wei (Relations industrielles / Industrial Relations, 2023)
An organization expects its employees to comply with job standardization to improve its production efficiency, while also expecting them to make suggestions to improve their job performance. Are the two goals compatible? Does job standardization turn employees into active speakers or stifled ones? This study is about how and why job standardization influences employee voice. I use conservation of resources (COR) theory to articulate competing hypotheses and a mediating process for the individual mechanism of employees’ role orientation in their job. In a three-wave panel survey, 232 employees completed questionnaires. The results are consistent with the resource conservation argument of COR theory: job standardization is resource-depleting and tends to narrow the role orientation of employees, who thus focus on resource conservation to fulfill job requirements and are in turn less likely to consume resources and voice suggestions. This study provides a specific, job-related way for managers to keep employee voice from being stifled or ignored. Job standardization should consider the relative importance of employee voice and be classified as discipline-related or job-content-related.
Keywords: conservation of resources; employee voice; job standardization; role orientation

L’accompagnement syndical des mobilisations de chauffeurs VTC et de livreurs de repas en France. Les apports d’une perspective comparative et intersectionnelle - Marchadour, Guénolé (Relations industrielles / Industrial Relations, 2023)
Le développement du travail de plateforme a vu naître, dans différents contextes nationaux, des mobilisations pour défendre les intérêts et faire reconnaître les spécificités de travailleur·es situé·es aux marges des relations industrielles. L’objectif de cet article est d’examiner, suivant une perspective comparative et intersectionnelle, l’accompagnement syndical des mobilisations de chauffeurs VTC et de livreurs de repas en France. À partir d’une enquête qualitative sur des collectifs suivis par la CFDT et la CGT, il met en évidence les défis et les obstacles communs auxquels ces organisations sont aujourd’hui confrontées pour soutenir l’action collective de travailleur·es précaires et racisé·es.
Keywords: Accompagnement syndical; Intersectionality; Intersectionnalité; Mobilisations; Mobilizations; Platform workers; Precariousness; Précarité; Travailleurs de plateforme; Union support

Comprendre les conflits liés à la réglementation du travail sur plateforme numérique : une revue critique de la littérature sur le rôle des institutions, des réseaux et des cadres cognitifs dans l’élaboration des politiques - Martin-Caballero, Angel (Relations industrielles / Industrial Relations, 2023)
La croissance du travail sur plateforme numérique a perturbé et réorganisé la réglementation sur l’emploi. La littérature a abordé ce sujet sous différents angles, mais souvent de manière fragmentée et sans expliquer clairement pourquoi et comment les conflits sur le plan réglementaire à propos du travail sur plateforme numérique surviennent. En utilisant le cadre de Beckert (2010) pour étudier la manière dont les domaines changent, l’auteur a effectué une revue critique de la littérature sur : 1) les rôles des institutions, des réseaux et des cadres dans la réglementation du travail sur plateforme numérique; 2) le pouvoir de réglementation que ces structures confèrent aux acteurs et aux organisations; et 3) les interrelations possibles entre ces structures. Les résultats démontrent l’existence d’une littérature abondante sur la portée de la réglementation institutionnelle et le pouvoir réglementaire des réseaux, mais beaucoup moins sur le rôle plus large de l’État dans ce domaine et les cadres qui guident les préférences des acteurs en matière de réglementation. Les axes de la recherche à réaliser dans le futur sont abordés.
Keywords: conflit réglementaire; revue critique de la littérature; réglementation; travail sur plateforme numérique

Understanding Conflict over Regulation of Platform Work: a Critical Literature Review on the Role of Institutions, Networks and Frames in Policy-Making - Martin-Caballero, Angel (Relations industrielles / Industrial Relations, 2023)
The expansion of platform work has disrupted and reordered employment regulation. The literature has contributed to this subject from different angles, although often in a fragmented way and without clearly explaining why and how regulatory conflict arises over platform work. Using Beckert's (2010) framework for study of how fields change, the author conducted a critical literature review on: 1) the roles of institutions, networks and frames in regulating platform work; 2) the regulatory power these structures provide to actors and organizations; and 3) the possible interrelationships between these structures. The results show the existence of a substantial literature on the scope of institutional regulation and the regulatory power of networks, but much less on the broader role of the state in this field, and the framing processes that guide the actors’ preferences for regulation. Future lines of research are discussed.
Keywords: critical literature review; platform work; regulation; regulatory conflict

Prison and the Work Ethic - McElligott, Greg (Labour / Le Travail, 2023)
Despite persistent depictions to the contrary, coercion pervades the modern work experience and, in many significant respects, is underwritten by the power of the state. This article outlines some of the ways in which long-standing interventions by Canadian (and British) states continue to affect workplace relations today. To appreciate the scope of this effect, it is necessary to trespass across a number of disciplinary boundaries to include topics such as immigration, deportation, political policing, the legal foundations of employment law, the continuing influence of the British Poor Laws, and the role of prisons and prison labour in helping to regulate work standards. States acted to support proletarianization in a comprehensive way, but their tendency to favour large-scale, "labour-saving" building projects has often undermined the actual effectiveness of their efforts at social control. These patterns still haunt prison policy, as I will show toward the end of the article in discussing the Toronto South Detention Centre.
Keywords: détérioration institutionnelle; institutional decay; labour policy; policy failure; politique du travail; prisons à haute sécurité; supermax prisons; travail forcé; unfree labour; échec de politique

Curated Decay: Residual Industrialization at the Nova Scotia Museum of Industry - McInnis, Peter S. (Peter Stuart) (Labour / Le Travail, 2023)
Nova Scotians understand economic hardships at both the personal and community levels. This is especially true for the residents of Pictou County. With the eclipse of coal, steel, and heavy manufacturing, successive governments looked to tourism to augment an eroding economic base and to commemorate the working lives of Nova Scotians. This article offers an analysis of the initial decision to construct and maintain the Museum of Industry in a region of the province subjected to sequential phases of deindustrialization. The venture, officially opened to regular attendance in 1995, is the largest facility in the province’s impressive system of 28 regional museums. The creation of the museum, however, was fraught with uncertainty and narrowly avoided financial collapse and plans to disperse the collection of artifacts. The project was subsequently left straddling an uneasy divide between celebrating industrial heritage and tempering controversies of economic and environmental development. Despite Nova Scotia’s proud heritage of worker resistance and union activism, visitors may exit the museum with the ambiguous message that while working lives are often harsh and riven with uncertainty, optimism for the future must prevail. The implication is that the appropriate response is selective anodyne forms of nostalgia, even resignation, but not resentment of the human and environmental costs of deindustrialization.
Keywords: coal mining; critical museum studies; deindustrialization; industrialization; public history; regional development; working-class commemoration

Ineligible: Single Mothers Under Welfare Surveillance - McKeen, Wendy (Labour / Le Travail, 2023)
The article reviews the book, "Ineligible: Single Mothers Under Welfare Surveillance," by Krys Maki.

Low Class Oil Trash and the Politico-Aesthetics of the Fossilized Proletariat - McLean, Jacob (Canadian Literature, 2023)
In the context of the climate crisis and the rise of the far right, scholars have warned of a "nascent fossil fascism" that combines far right authoritarian politics with fossil fuel boosterism (Daggett). In Canada, this conjuncture expresses itself, in part, through extractive populism, a reactionary political project to counter the environmental left (Gunster et al.). Low Class Oil Trash stands out among other extractive populist entities for its foray into cultural production, having written and produced an original song, "Gassed Up," an "anthem for the oil and gas industry." This article does a close reading of "Gassed Up" and Low Class Oil Trash's social media posts. I use Andreas Malm and the Zetkin Collective's terms "fossilized proletariat," "fossilized whiteness," and "fossilized masculinity" to analyze these petrocultural products, exploring why some members of the working class, despite the threat of climate change, cling to fossil fuels.

Le syndicalisme japonais à l’épreuve du capitalisme de plateforme - Nakano, Kenshin (Relations industrielles / Industrial Relations, 2023)
Dans un contexte mondial où l’expansion de l’économie de plateformes numériques dans les secteurs du transport de personnes et de la livraison de repas suscite les mobilisations des travailleurs, le contexte japonais est caractérisé par une double « étrangeté », à savoir une absence apparente des travailleurs de plateformes dans le secteur du transport de personnes alors que les mobilisations y ont été importantes et une faible mobilisation dans le secteur de la livraison de repas où le nombre de livreurs a véritablement explosé. À partir d’une enquête qualitative menée auprès de divers acteurs actifs dans les deux secteurs, l’article montre comment le syndicalisme japonais a réagi face au capitalisme de plateforme.
Keywords: Japan; Japon; Travailleurs de plateforme; Uber; digital platforms; food delivery workers; livreurs de repas; plateformes numériques; platform workers; syndicat; taxi; trade union

How We Struggle: A Political Anthropology of Labour - Nasari, Pedrom (Labour / Le Travail, 2023)
The article reviews the book, "How We Struggle: A Political Anthropology of Labour," by Sian Lazar.

"Lawless Coal Miners" and the Lingan Strike of 1882–1883: Remaking Political Order on Cape Breton's Sydney Coalfield - Nerbas, Don (Labour / Le Travail, 2023)
The Lingan strike of 1882–83 was the last in a series of strikes over a two-decade period on Cape Breton Island's Sydney coalfield. With the use of untapped local sources, this article reconstructs the history of this understudied strike within a broader history of social relations on the coalfield. The migration of labourers from the island's backland farms – predominantly from Highland enclave settlements – to the coal mines played a decisive role in shaping the era's new coal mining villages and the character of social conflict. By the early 1880s, structural change associated with National Policy industrialism was eroding the old authority of the coal operators, and miners embraced the Provincial Workmen's Association (pwa) to advance their claims in long-standing and highly localized contestations. Ultimately the coal communities themselves imposed the emergent trade unionism. The Lingan strike marked a transition to a new political order on the coalfield, structured by the place of the coal mines within the wider Cape Breton countryside and built upon a powerful localism and moral economy that recast the public sphere and the miners' place in it.
Keywords: Cape Breton; Nouvelle-Écosse; Nova Scotia; capitalism; capitalisme; charbon; coal; grèves; labour; mines; mining; moral economy; riots; strikes; travail; économie morale; émeutes

Editors’ Note = Note de la rédaction [91, Fall 2023] - Niergarth, Kirk; Smith, Charles (Labour / Le Travail, 2023)
Welcomes guest editors Lachlan MacKinnon and Steven High to the special issue on deindustrialization.

Teresa Rosemary Healy: Feminist, Labour Scholar, Activist, Musician - O'Manique, Colleen (Labour / Le Travail, 2023)
Pays homage to the wide-ranging interests of the activist and scholar, Teresa Healy (1962-2022).

The Right to Disconnect from Work in Canada: Section 21.1.1 of Ontario’s Employment Standards Act in Context - Ogunde, Fife (The Canadian Bar Review, 2023)
Ontario’s provincial government enacted legislation in 2021 mandating employers to develop and maintain workplace policies with regard to employees disconnecting from work. The aim of this article is to examine the suitability of Ontario’s legislative response under the Employment Standards Act in the context of the “right to disconnect”. This paper argues that the Canadian “right to disconnect” in its current form is inadequate from a regulatory perspective and advocates for a stronger framework in this respect.

Prendre soin de la famille émancipée. La santé des affranchis et sa négociation à l'aube de la Reconstruction au Tennessee (1862–1866) - Ouellet, Nelson (Labour / Le Travail, 2023)
Dans cet article, les contrats de travail signés au Tennessee par les propriétaires fonciers et les affranchis sont placés au centre d'une étude sur un paradoxe de la liberté aux États-Unis. Nous soutenons l'idée que la santé des affranchis – qui comprend les soins médicaux, la subsistance et la protection physique – se négocie durant et après la guerre de Sécession dans le but d'assujettir les intérêts des Noirs, de l'État et des propriétaires terriens à un idéal de relations sociales de production régi par la liberté, le droit et le marché. En examinant les contrats de travail et leurs clauses médicales, nous revisitons l'approche médico-politique qui a maintes fois conduit les historiens à la thèse de l'échec de la Reconstruction. Nous plaçons aussi la famille noire dans le processus d'émancipation et de production par la voie des contrats et d'une relecture de la « culture de la dissimulation » proposée par l'historienne Darlene Clark Hine il y a plus de trente ans. Enfin, nous nous éloignons d'une lecture qui réduit les contrats à la seule oppression dont étaient victimes les Noirs après la guerre de Sécession. En complément, nous invitons le lecteur à examiner les débats sur la citoyenneté qui ont suivi la ratification du treizième amendement.
Keywords: African Americans; Noirs; Reconstruction; contracts; contrats; famille; family; freedom; health; santé; travail; work; émancipation

A Hero from Capitalism’s Hells: Mike Davis and the Fighting Spirit of Socialist Possibility - Palmer, Bryan D. (Labour / Le Travail, 2023)
An illustrated, life-and times portrait of Mike Davis (1946-2022), the American writer, activist, urban theorist, and historian.

Civilization: From Enlightenment Philosophy to Canadian History - Palmer, Bryan D. (Labour / Le Travail, 2023)
The article reviews the book, "Civilization: From Enlightenment Philosophy to Canadian History," by Elsbeth A. Heaman.

Éclairage par le commun des conditions organisationnelles pour la pérennité des communautés de pratique - Pastier, Kévin; Combes, Victor; Dalmas, Michel; Silva, François (Relations industrielles / Industrial Relations, 2023)
Objectif de la recherche : Cet article interroge la pérennité des communautés de pratique (CoP), généralement considérée par des approches déterministes, en utilisant le cadre théorique des communs. Cet article propose donc par analogie d’analyser les CoP en tant qu’organization et organizing. Cette approche doit permettre d’identifier les conditions internes pour une reproduction d’une CoP. L’objectif de cette recherche est ainsi de comprendre les conditions d’auto-organisation et de pérennité d’une CoP. Méthodologie : Pour ce faire, nous utilisons une méthodologie mixte. Après une étude qualitative de plusieurs mois à observer et analyser deux CoP, nous nous appuyons sur une étude quantitative menée auprès de sept CoP au sein d’une entreprise, MUTUALIS. Un questionnaire permettant d’analyser l’organization et l’organizing des CoP a été envoyé aux membres. 76 réponses ont été retenues et analysées avec SMART PLS. Contribution : Si cet article identifie un potentiel de reproduction interne des CoP et donc de pérennité, il souligne également que celle-ci demeure partielle par son usage instrumental. En raison de ce dernier, les CoP minimisent leur reproduction organisationnelle et donc leur auto-organisation. Pour dépasser cette limite, le cadre du commun propose in fine une approche intégrative de l’organisation d’une action collective auto-organisée qui nous amène à penser la démocratisation à une échelle multiniveaux. Finalement, cette étude démontre l’impératif d’une transformation organisationnelle plus générale de l’entreprise qui ne peut être réduite à des dispositifs ou des communautés sporadiques.
Keywords: Commoning; Communauté de pratique; Community of practice; Degeneration; Dégénérescence; Mixte analysis; Méthodologie mixte

Cycles de risque, capitalisme et avenir du travail - Peetz, David (Relations industrielles / Industrial Relations, 2023)
Cet article interprète les nombreuses données empiriques sur la croissance, puis la stagnation des « modes de flexibilité » à l’aide de la théorie du procès de travail, en particulier en ce qui concerne le contrôle et la résistance. Dans un « cycle de risque », la direction saisit d’abord une occasion de réduire les coûts en transférant le risque du capital au travail par le biais d’un certain mode de flexibilité. Le mode choisi est de plus en plus utilisé jusqu’à ce que l’expansion soit bloquée par la nécessité de vaincre la résistance, d’obtenir le consentement et/ou d’exercer un contrôle. La direction cherche alors un nouveau mode. Le cycle de risque est cohérent avec les données de l’OCDE sur l’« emploi temporaire » et les données australiennes sur l’« emploi occasionnel ». Les implications pour l’économie à la demande et l’avenir du travail sont abordées.
Keywords: contrôle; cycle du risque; emploi occasionnel; emploi temporaire; flexibilité; précarité; résistance

Risk Cycles, Capitalism and the Future of Work - Peetz, David (Relations industrielles / Industrial Relations, 2023)
This paper interprets extensive empirical data on the growth and then stagnation of “modes of flexibility” by using labour process theory, specifically with respect to control and resistance. In a “risk cycle,” management initially seizes an opportunity to reduce costs by transferring risk from capital to labour through some mode of flexibility. The chosen mode is used more and more until further expansion is blocked by the need to overcome resistance, to obtain consent and/or to exercise control. Management then seeks a new mode. The risk cycle is consistent with OECD data on “temporary employment,” and Australian data on “casual employment.” Implications for the gig economy and the future of work are discussed.
Keywords: casual employment; control; flexibility; precarity; resistance; risk cycle; temporary employment

Les couleurs de la révolution. La gauche à l’épreuve du pouvoir. Venezuela, Équateur, Bolivie : un bilan à travers l’histoire - Peñafiel, Ricardo (Labour / Le Travail, 2023)
The article reviews the book, "Les couleurs de la révolution. La gauche à l’épreuve du pouvoir. Venezuela, Équateur, Bolivie : un bilan à travers l’histoire," by Patrick Guillaudat and Pierre Mouterde.

Putting Skill to Work: How to Create Good Jobs in Uncertain Times - Pérez-Lauzon, Sara (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Putting Skill to Work: How to Create Good Jobs in Uncertain Times," by Nichola Lowe.

Frontiers of Feminism: Movements and Influences in Québec and Italy, 1960–1980 - Raby, Marie-Laurence (Labour / Le Travail, 2023)
The article reviews the book, "Frontiers of Feminism: Movements and Influences in Québec and Italy, 1960–1980," by Jacinthe Michaud.

The Flows of Racial Capitalism: Charting the Spread of COVID-19 through Alberta’s Meatpacking Industry - Rinaldi, Jen; Fernando, Shanti (Journal of Critical Race Inquiry, 2023)
This article will present a case study of Cargill’s High River meatpacking plant operations to show how at crucial historical junctures racial capitalism shaped its working conditions and in so doing determined the spread of COVID-19. First, the Canadian meatpacking industry’s 1980s-era economic restructuring relocated and reorganized its workforce from a core to peripheral one, allowing for the low wage employment of many precarious workers; this restructuring enabled the Cargill company to gain overwhelming control of the meatpacking industry in Canada and to become a “choke point” in the supply chain. Second, Canadian immigration policy from 2006 to 2010 supported a marked increase in migrant workers to meet the labour market needs of business; this reconstituted the labour class to heighten their disposability. With these pieces in place, the Albertan provincial government could classify meatpackers as “essential workers” who worked even in the face of mass COVID infection in April through June 2020. Across this crucial historical period racial capitalism enabled the plant to circumvent public health interventions protecting workers through the onset of the pandemic. Political championing of business interests, enacted through legislative mechanisms, allowed for the exploitation of workers and consistently rendered workers personally responsible for their own health and safety, despite their lack of control over what exposed them to risk.

Justice at Work: The Rise of Economic and Racial Justice Coalitions in Cities - Roth, Silke (Labour / Le Travail, 2023)
The article reviews the book, "Justice at Work: The Rise of Economic and Racial Justice Coalitions in Cities," by Mark Doussar and Greg Schrock.

Work and the Carceral State - Rouleau, Alexis Marcoux (Labour / Le Travail, 2023)
The article reviews the book, "Work and the Carceral State," by Jon Burnett.

Waitresses in Action: Feminist Labour Protest in 1970s Ontario - Sangster, Joan (Labour / Le Travail, 2023)
In the 1970s, women in Toronto created the Waitresses Action Committee to protest the introduction of a "differential" or lower minimum wage for wait staff serving alcohol. Their campaign was part of their broader feminist critique of women's exploitation and the gendered and sexualized nature of waitressing. Influenced by their origins in the Wages for Housework campaign, they stressed the linkages between women's unpaid work in the home and the workplace. Their campaign eschewed worksite organizing for an occupational mobilization outside of the established unions; they used petitions, publicity, and alliances with sympathizers to try to stop the rollback in their wages. They were successful in mobilizing support but not in altering the government's decision. Nonetheless, their spirited campaign publicized new feminist perspectives on women's gendered and sexualized labour, and it contributed to the ongoing labour feminist project of enhancing working-class women's equality, dignity, and economic autonomy. An analysis of their mobilization also helps to enrich and complicate our understanding of labour and socialist feminism in this period.
Keywords: Wages for Housework; féminisme de deuxième vague; lois sur le salaire minimum; minimum-wage laws; salaire au travail ménager; second-wave feminism; syndicalisation des serveuses; waitress organizing

Platforms and the Challenges for Workers’ Digital Action: The Brazilian Experience during the COVID-19 Pandemic - Santana, Marco (Relations industrielles / Industrial Relations, 2023)
In this article, I will analyze the ways in which Brazilian workers are using social media to organize and mobilize. Although analysis of social media use has made great progress, in the case of worker movements it still needs further development. I will focus on the experience of Brazilian app-based delivery workers during the COVID-19 pandemic. Despite their dispersion across the country, delivery workers were able to carry out two national strikes through intense use of WhatsApp, Facebook, YouTube and Twitter. Using qualitative analysis of posts from worker organizations on social media, it was possible to identify the challenges faced by these movements when using digital media. Social media helped solve some organizational and communication problems, while producing others that workers had to deal with.
Keywords: Action collective; Brazil; Brésil; Livreurs; Mobilisation en ligne des travailleurs; Plateformes numériques; collective action; delivery workers; digital platforms; workers’ digital action

"I Felt like I Was Losing Every Day": Women Educators' Lived Experience of the COVID-19 Pandemic - Smith, Julia (Labour / Le Travail, 2023)
The covid-19 pandemic severely disrupted the education system in Canada from March 2020 throughout the 2020–21 school year. It also had disproportionate secondary effects on women in terms of unpaid care, economic loss, and poor mental health. This article explores the lived experience of women educators in the province of Alberta, drawing on interviews and focus groups with 39 educators. Findings indicate that the pandemic not only exacerbated the triple burden that women educators, in particular, bear but added additional layers of responsibility related to public health management, educating children at home, elder care responsibilities, and emotional labour. The essential role women educators fulfilled within the covid-19 response, at work and at home, cost them time, professional development opportunities, mental wellness, and the positive rewards that had drawn them to the educational field. Current concerns around educator burnout and retention may be mitigated by acting on the recommendations of women educators regarding the development of more equitable education systems and social policy.
Keywords: Alberta; Canada; care economy; covid-19; education; feminist; femmes; féministe; gender; genre; health; santé; women; économie des soins; éducation

La capture des travailleurs à l’ère du travail précaire : réduire le taux de roulement en l’absence de l’engagement et de la sécurité d’emploi des employés - St-Denis, Xavier (Relations industrielles / Industrial Relations, 2023)
Le présent article soutient que la rétention du personnel demeure une priorité essentielle pour de nombreux employeurs, même si ces derniers deviennent de moins en moins enclins à offrir des emplois stables. La recherche a montré que, face à cette précarité croissante de l’emploi, les travailleurs adoptent des stratégies individuelles de progression professionnelle axées sur la mobilité entre entreprises, lesquelles viennent renforcer les inquiétudes des employeurs en ce qui concerne le roulement du personnel. Cet article défend l’importance pour les chercheurs en relations industrielles d’étudier de plus près les pratiques organisationnelles qui restreignent la mobilité des employés, c’est-à-dire les « stratégies de capture des travailleurs ». Celles-ci se distinguent des autres pratiques en matière de mobilité du fait qu’elles sont unilatérales et qu’elles visent une réduction du roulement du personnel sans nécessairement chercher à favoriser un sentiment d’engagement ou de loyauté chez les employés.
Keywords: Insécurité d’emploi; carrière; clause de non-concurrence; flexibilité du travail; roulement du personnel; rétention du personnel

Worker Capture in the Precarious Work Era: Reducing Turnover without Employee Commitment and Job Security - St-Denis, Xavier (Relations industrielles / Industrial Relations, 2023)
This paper argues that employee retention remains a key priority for many employers, even as they become less likely to offer stable employment. In the face of increased job insecurity, researchers have shown that workers have adopted personalized career progression strategies that emphasize inter-firm mobility. Such strategies heighten employer concerns about employee turnover. The paper argues that the industrial relations literature would gain from closer study of organizational practices that restrict employee mobility, i.e., “worker capture strategies.” Such practices stand out from other mobility-reducing ones because they are unilateral and aim to reduce turnover without necessarily fostering a sense of commitment or loyalty among employees.
Keywords: careers; flexible employment; job insecurity; non-compete agreements; retention; turnover

La virtualisation des communications en contexte de travail hybride : un effet d’entraînement ou de réduction des comportements hostiles ? - St-Onge, Sylvie; Bachini, Eva (Relations industrielles / Industrial Relations, 2023)
Depuis la pandémie, un nombre croissant d’employés travaillent partiellement ou totalement à distance et en présentiel selon leur volonté ou des balises définies par leur employeur. Cette étude explore (1) les liens entre l’adoption de ces modes de travail qualifiés d’« hybride » (un changement d’organisation du travail important qui a modifié, entre autres, les lieux, les heures et la charge de travail) et diverses formes de comportement hostiles parmi le personnel ; (2) les moyens de prévenir et contrer l’émergence de comportements hostiles dans un contexte de travail hybride appelé à s’intensifier.
Keywords: Remote work; aggression; agression; bullying; cyberbullying; cyberharassment; cyberharcèlement; harassment; harcèlement; incivility; incivilités; telecommuting; travail à distance; télétravail

Refinery Town in the Petrostate: Organized Labour Confronts the Oil Patch in Western Canada - Stevens, Andrew; Nesbitt, Doug (Studies in Political Economy, 2023)
In 2019, Regina’s Co-operative Refinery Complex locked out the 730 members of Unifor Local 594 amid record profits in an aggressive drive for significant pension concessions. Marred by sweeping antipicketing injunctions, an enormous scab operation, police repression, and general public enmity, the lockout suggests two overlapping trends. First, the union’s adherence to co-operative and conciliatory bargaining had left it ill equipped to confront—either in the workplace or the public sphere—management’s costcutting agenda in the centre of Saskatchewan’s now hegemonic petrostate. Second, a marked tension developed between community outreach efforts and the circumstances in which legal industrial action was ineffective and civil disobedience emerged.
Keywords: Collective action; just transition; oil unionism; petrostate; revitalization; union renewal

Organizing Informal Workers Globally: Comparing a Global Union Federation and a Global Informal Worker Organization Network - Tilly, Chris (Relations industrielles / Industrial Relations, 2023)
With economic globalization and with the precarization and informalization of work, efforts have increased to build global labour alliances among formal workers on the one hand and to organize informal workers on the other. These two endeavours overlap considerably. Global labor organizations have taken on a growing role in organizing and advocating for informal workers. I explore this overlap by comparing two global labour federations: one arising from heterogeneous networks of informal workers—the International Domestic Workers Federation—and a longstanding one of formal employees that has increasingly attempted to include informal workers—the Building and Wood Workers International. The contrast reveals similarities, divergences and trade-offs, with important implications for the future potential for building global organizations of informal workers.
Keywords: Construction workers; domestic workers; global unions; informal work; power resources

Inequality in Canada: The History and Politics of an Idea - Tough, David (Labour / Le Travail, 2023)
The article reviews the book, "Inequality in Canada: The History and Politics of an Idea," by Eric W. Sager.

Franchising and the Extraction of Surplus Value: Excavating the Legal Boundary Between Franchisees and Employees - Tucker, Eric; Bartkiw, Timothy J. (Journal of Law and Political Economy, 2023)
Nearly one in ten Canadians in the private sector works in the franchised sector of the economy. For the most part, franchisors operate as rentiers, extracting value from franchisees for the use of their brand. Research has demonstrated that this arrangement puts additional pressure on franchisees to extract surplus value from their employees that tend toward substandard and unlawful working conditions. In this scenario, franchisors benefit from but are only indirectly involved in the extract of surplus value. In some cases, however, the vertical controls exercised by “franchisors” over “franchisees” are so extensive, and the financial contribution of “franchisees” is so limited, that the franchisor becomes involved in directly extracting surplus value from franchisees. We explore this latter phenomenon through an excavation of the history of the legal distinction in Canadian business-format franchising in Canada and detailed studies of two recent Canadian cases in which “franchisees” successfully claimed employment status.

A Crusading Voice for the Mining West: How the Rossland Evening World Served Militant Workers at the Turn of the 20th Century - Verzuh, Ron (Labour / Le Travail, 2023)
The Rossland Evening World, a four-page daily dedicated to the mineworkers of British Columbia's bustling West Kootenay mining town of Rossland, first appeared on May Day 1901 – just in time to do battle with local mine owners in the historic 1900–01 miners' strike. The World may have owed its existence in part to William "Big Bill" Haywood, a founder of the militant Western Federation of Miners (wfm) and the Industrial Workers of the World. On visiting the town and the prospectors' camp in the 1890s, Haywood saw that Rossland would soon grow into a thriving Pacific Northwest mountain community with a steady increase in wfm membership. He encouraged the miners to form wfm Local 38, possibly the first wfm local in Canada, and soon a dozen Kootenay locals formed wfm District Association 6. A wfm grant followed to help launch the local and the new daily. Amid growing frustration with bad working conditions and mine owners' refusal to recognize the wfm, the World became a welcome sister to the wfm's Miners' Magazine, dedicating itself to "the Interests of Organized Labor." By the fall of 1900, the strike of 1,400 miners was on, and the World published news and analysis throughout the region. Ultimately the strike was lost, but the World carried on until 1904. As its legacy, it showed how a daily newspaper could help build community support and provide a defence for the local unionized workforce.
Keywords: 1901 strike; Big Bill Haywood; Kootenay; Rossland; Western Federation of Miners; Wobblies; grève de 1901; industrie minière; journalisme syndical; labour journalism; mining; réduction du temps de travail; shorter hours

Through the Back-Door: How Australia and Canada Use Working Holiday Programs to Fulfill Demands for Migrant Work Via Cultural Exchange - Vosko, Leah F. (Journal of Industrial Relations, 2023)
In Australia and Canada, working holidaymaking is rationalized on the basis of encouraging cultural exchange among youth. Yet, in both countries, there is mounting evidence that working holiday programs are operating as back-door migrant work programs to help fill demands for labor in occupations and industries characterized by precarious jobs undesirable to locals. As scholarship on working holidaymakers’ labor market participation is more developed in Australia than in Canada, and administrative data available are also more extensive therein, this article sheds new light on the Canadian case vis-à-vis the Australian example. In exploring regulatory strategies adopted by these two settler states and their effects, comparative analysis of administrative data and historical and contemporary immigration and labor and employment laws and policies reveals how nationally specific program design can foster similar ends: precariousness among participants in the industries in which working holidaymakers are concentrated, including agriculture, tourism, and accommodation and food services. It also shows that stratification between working holidaymakers more closely approximating the image of the “cultural sojourner” and those who are effectively migrating for work purposes takes shape principally along the lines of source country in both countries.

Le capital algorithmique. Accumulation, pouvoir et résistances à l’ère de l’intelligence artificielle - Vultur, Mircea (Relations industrielles / Industrial Relations, 2023)
The article reviews the book, "Le capital algorithmique. Accumulation, pouvoir et résistances à l’ère de l’intelligence artificielle," by Jonathan Durand Folco and Jonathan Martineau.

Labour and the Law in Canada, an Essay by Maurice Spector - Wentzell, Tyler (Labour / Le Travail, 2023)
Introduces Spector's essay on labour law, written from a Marxist perspective while he was attending Osgoode Hall law school in the early 1930s. Provides biographical background on Spector, a former Communist who became a leading Canadian Trotskyist. He briefly practiced law in Toronto before moving to New York in the later 1930s.

Reckoning with Racism: Police, Judges and the RDS Case - Whitehead, Robin (Labour / Le Travail, 2023)
The article reviews the book, "Reckoning with Racism: Police, Judges and the RDS Case," by Constance Backhouse.

White Space: Race, Privilege, and Cultural Economies of the Okanagan Valley - Yakashiro, Nicole (Labour / Le Travail, 2023)
The article reviews the book, "White Space: Race, Privilege, and Cultural Economies of the Okanagan Valley," edited by Daniel J. Keyes and Luís L.M. Aguiar.

Football in the Land of the Soviets - Zohn, Yacov (Labour / Le Travail, 2023)
The article reviews the book, "Football in the Land of the Soviets," by Carles Viñas.